2014
DOI: 10.1155/2014/853084
|View full text |Cite
|
Sign up to set email alerts
|

Molybdenum Reduction to Molybdenum Blue inSerratiasp. Strain DRY5 Is Catalyzed by a Novel Molybdenum-Reducing Enzyme

Abstract: The first purification of the Mo-reducing enzyme from Serratia sp. strain DRY5 that is responsible for molybdenum reduction to molybdenum blue in the bacterium is reported. The monomeric enzyme has an apparent molecular weight of 105 kDalton. The isoelectric point of this enzyme was 7.55. The enzyme has an optimum pH of 6.0 and maximum activity between 25 and 35°C. The Mo-reducing enzyme was extremely sensitive to temperatures above 50°C (between 54 and 70°C). A plot of initial rates against substrate concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 34 publications
3
36
0
Order By: Relevance
“…This is similar to all isolated Mo-reducing bacteria that have been reported, exhibiting optimal conditions from the lowest pH at 5.0 to the highest pH at 7.0 [15,[29][30][31][32][33][34]. As the stability and formation of phosphomolybdate are optimal under acidic conditions, determination of optimal pH plays a significant role.…”
Section: Optimum Temperature and Ph On Molybdenum Reductionsupporting
confidence: 83%
See 4 more Smart Citations
“…This is similar to all isolated Mo-reducing bacteria that have been reported, exhibiting optimal conditions from the lowest pH at 5.0 to the highest pH at 7.0 [15,[29][30][31][32][33][34]. As the stability and formation of phosphomolybdate are optimal under acidic conditions, determination of optimal pH plays a significant role.…”
Section: Optimum Temperature and Ph On Molybdenum Reductionsupporting
confidence: 83%
“…Based on previous studies, the phosphate concentration required is around 5 mM and lower for optimal Mo-reduction [13,15,18,23,28,[30][31][32][33][34][35][36][37]39]. The result of the present study showed that maximum concentration of phosphate also occurred at 5.0 mM.…”
Section: Effect Of Phosphate and Molybdate Concentration On Moreductionsupporting
confidence: 58%
See 3 more Smart Citations